Influence of diverse finishing systems on carcass characteristics, proximate composition, and meat quality attributes of striploins from bison heifers - O’Sullivan, Lydia M.; Anema, Reid F.; Weldy, Garrett T.; Carpenter, Benjamin J.; Hernandez, M. Sebastian; Underwood, Keith R.; Grubbs, Judson K.; Bakker, Christina E.; Legako, Jerrad F.; Lovitt, Jessica; Kruse, Carter; Blair, Amanda D. (Frontiers in Ecology and Evolution, 2025)
Bison producers commonly utilize grain- or grass-finishing across both extensive and intensive management systems that can vary in diet composition and nutrient concentration. Finishing systems may impact the growth rate and composition of gain, as well as tenderness and sensory characteristics of bison meat. Therefore, the objective of this study was to determine the effect of diverse finishing systems on carcass composition and meat quality of bison. Bison heifers (n = 263, approximately 25 months of age) from a single source were randomly assigned to one of six finishing systems: 1) pen-finished with free choice access to each feedstuff (grass hay, alfalfa, and corn grain in separate feeders) at low stocking density (55 m2 per animal, n = 45); 2) pen-finished with grass hay, alfalfa, and corn provided as a total mixed ration (TMR) at low stocking density (n = 43); 3) pen-finished with the same TMR at high stocking density (27 m2 per animal, n = 44); 4) range-finished on high diversity rangeland (n = 44); 5) range-finished on low diversity rangeland (n = 44); and 6) range-finished on low diversity rangeland with free choice access to corn supplement (n = 43). At approximately 31-32 months of age, all heifers were transported to a commercial harvest facility. Carcass data were recorded, and one striploin was collected from a subsample of carcasses for analysis of composition, meat tenderness, and trained sensory panel evaluation. Addition of corn grain increased live weight, carcass weight, dressing percentage, ribeye area, and backfat thickness compared with heifers finished only on rangeland. Finishing systems did not influence objective tenderness. Pen-finishing systems that included corn grain improved perception of several sensory attributes including juiciness, brown/roasted, sweetness, and umami, whereas the intensity of characteristic bison flavor was more prominent in range-finished bison. However, corn supplementation on rangeland, pen stocking density, rangeland diversity, and pen-based feed delivery rarely influenced sensory attributes. Collectively, finishing systems influenced many bison carcass composition and meat characteristics, suggesting that bison meat products from differing finishing systems could influence economic outcomes of bison enterprises and provide alternative marketing opportunities to meet varied consumer preferences.